2004
DOI: 10.1017/s0033291704002818
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health of Australian veterans of the 1991 Gulf War: an assessment using the SF-12, GHQ-12 and PCL-S

Abstract: Background. Elevated rates of psychological morbidity and symptomatology have been widely reported in 1991 Gulf War veterans. The present study used brief self-report instruments to compare the psychological health of Australian Gulf War veterans with that of a randomly sampled military comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…The youngest veterans also were most likely to report coming under actual attack. These findings may be relevant to previous military research which has identified younger age at time of deployment as a risk factor for PTSD (Brewin et al, 2000) and lower rank as a risk factor for psychological ill health (Ismail et al, 2000;McKenzie et al, 2004).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The youngest veterans also were most likely to report coming under actual attack. These findings may be relevant to previous military research which has identified younger age at time of deployment as a risk factor for PTSD (Brewin et al, 2000) and lower rank as a risk factor for psychological ill health (Ismail et al, 2000;McKenzie et al, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…The methods presented in this article are part of a larger study investigating a wide range of health outcomes and exposures; these are more fully described elsewhere Kelsall et al, 2004;McKenzie et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is intriguing because several questionnaire-based studies [21][22][23][24][25][26] have suggested such a difference, although the GW itself was not traumatic for the majority of the coalition forces, and certainly not in the context of other major armed conflicts. Unlike the situation after, for example, Vietnam, the media representations of the consequences of the service in the Gulf have tended to focus on possible environmental, as opposed to psychological/ traumatic, hazards in their reporting of the consequences of the GW.…”
Section: Discussionmentioning
confidence: 99%
“…The measure produces two summary scores, the SF-12 Physical Component Summary (PCS) and the SF-12 Mental Component Summary (MCS), which respectively assess the degree to which physical health and mental health problems have interfered with role functioning. The SF-12 has good reliability and validity [41] and has been used in military samples [42].…”
Section: Quality Of Lifementioning
confidence: 99%